(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Sub Arachnoid Block (SAB) is a frequently used popular anaesthetic technique but it is not without complications. The objectives of this retrospective descriptive study was to report and evaluate the complications of SAB in Khulna city,which occurred in a period of 5 years from January 2004 to December 2008. It was a multicentre study. Related data from anesthetic procedure records were collected for above mentioned period. Total 10829 patients were operated under SAB in those centres during the study period. Majority of patients were female (72.22%), mean age was 39 ± 9.78 years, age groups between 20 to 39 years were 72.22%, ASA physical status between I and II were 87.01%. Complications of SAB were mild hypotension 3090(28.53%), severe hypotension 83(0.76%), cardiac arrest 20(0.18%), postdural puncture headache (PDPH) 1825(16.85%), meningism 10(0.09%), cuada equina syndrome 4(0.036) and death 3(0.027%). Most common complications were simple hypotension and PDPH. Serious adverse events such as severe hypotension, cardiac arrest, cauda equina syndromes and death were were more than other western countries and may be due to shortage of adequate skilled anaesthesiologist. A prospective study with a good number of qualified anaesthesiologists can be taken in hand on ward for further evaluations. DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18177 Journal of BSA, 2009; 23(2): 67-71